A Note on the Riccati Equation - Cruz-Santiago, R.; López-Bonilla, J.; Morales, J. (Himalayan Physics, 2013)
We show the relationship between the solutions of two Riccati equations associated to Schrödinger equations interconnected via a Darboux transformation. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 32-33 Uploaded date: 12/23/2013